Influence of Surface Roughness on Strong Light-Matter Interaction of a Quantum Emitter-Metallic Nanoparticle System - Yu-Wei Lu (Nature Portfolio, 2018)
Abstract We investigate the quantum optical properties of strong light-matter interaction between a quantum emitter and a metallic nanoparticle beyond idealized structures with a smooth surface. Based on the local coupling strength and macroscopic Green’s function, we derived an exact quantum optics approach to obtain the field enhancement and light-emission spectrum of a quantum emitter. Numerical simulations show that the surface roughness has a greater effect on the near-field than on the far-field, and slightly increases the vacuum Rabi splitting on average. Further, we verified that the near-field enhancement is mainly determined by the surface features of hot-spot area.